2004
DOI: 10.1097/00004703-200410000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Can Neurobehavioral Examination Predict the Presence of Cerebral Injury in the Very Low Birth Weight Infant?

Abstract: This study examined in a regional cohort of 66 term age very low birth weight infants, the relationship between qualitative magnetic resonance imaging (MRI) measures of cerebral white and gray matter abnormalities and infant neurobehavioral functioning assessed by structured neurological examination. The diagnostic utility of the Dubowitz neonatal neurological examination in identifying children with severe cerebral abnormalities was also evaluated. Examination results revealed the presence of high rates of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 25 publications
2
23
1
10
Order By: Relevance
“…Similar results were found in a cohort study of 66 very low birthweight infants who also had MRI 16. These infants had a mean gestational age of 28 weeks at birth, and all had neurological examination and MRI at term equivalent age.…”
Section: Indications and Limitationssupporting
confidence: 84%
“…Similar results were found in a cohort study of 66 very low birthweight infants who also had MRI 16. These infants had a mean gestational age of 28 weeks at birth, and all had neurological examination and MRI at term equivalent age.…”
Section: Indications and Limitationssupporting
confidence: 84%
“…However, the discerning qualities of the NAPI suggest there is evidence to moderate the current thinking. Another recent study shows good relationship between neonatal exam and brain MRI, 25 and in an earlier study, we found a neonatal neuro exam at term age to be predictive of CP in high-risk preterm infants. 26 A cautionary note must be made to the effect that in general the more robust infants failed to return for assessment at 30 months.…”
Section: Discussionsupporting
confidence: 68%
“…24 Consistent with findings in other cohorts, the neuromotor scores at the time of the MRI were higher in those newborns with moderate to severe MRI abnormalities. 25 It is unknown whether the application of a more sophisticated scoring system of the preterm neonatal neurologic examination, such as the Dubowitz scale, 24 might improve the predictive value of the early exam.…”
Section: Discussionmentioning
confidence: 99%